EKSTRAKSI LILIN DAUN PINUS DENGAN TEKNOLOGI SUPERKRITIKALFLUIDA CO2 - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1995)
The objectives of this research is to study the influence of flushing activities on crude waxes yield, and to study the extraction of waxes from pine needles by using supercritical fluid C02 technology. The extraction was carried out at an 400C extraction temperature and at various extraction pressures. consisting of  9,14,24 and 30 MPa. Crude waxes were precipitated in the first cold trap at  6-7 MPa intermediate pressure and 00C, and the rest of  it was precipitated in the second cold trap at an 0,1 MPa with a similar temperature. After extraction, it was always followed by flushing activities  through two steps to get waxes which still remained in the valves and or in the line on the system. First flushing was performed with supercritical fluid extraction without any  sample  in  the  extraction  cell. The second flushing  was  conducted  with a chloroform solvent.  Pure waxes of were purified  and analysed by using High Performance Liquid Chromatography (HPLC).Results indicated that the flushing activities with supercritical fluid extraction without any sample in the extraction cell followed by a chloroform solvent had agreat effect on crude waxes yield. At a 30 MPa extraction pressure and at an 40°C extraction temperature, supercritical fluid extraction with flushing gave crude wax yield four time greater than the cude waxes yield obtained by supercritical fluid extraction without any flushing, even to the crude waxes yield from  the chlorofrom solvent extraction.  The increase in extraction pressure caused an increase in crude waxes, both  obtained from the first and  the second  cold  traps. Moreover,  HPLC analysis of pure waxes revealed  that the elution of pure waxes took 3.70 - 3.90 minutes. lt was also shown that an increase in extraction pressure led to an increase in pure waxes.